The Development of a Local Wisdom-Based Natural Science Comic Through a Webtoon to Improve Students’ Critical Thinking Skills - Kevin Aditia; Ahmad Muhlisin; suwito singgih (Indonesian Journal of Science and Education, 2022)
Critical thinking is a needed basic skill in the 21st century. This study aims to produce a local wisdom-b ased natural science learning medium with a theme of the story of an eclipse of Batara Kala through aW ebtoon to develop critical thinking skills. The medium development employs an ADDIE developmentp rocedure that consists of analysis, design, development, implementation, and evaluation. The result of validation from a media expert is 4.15, whereas the content expert validation is 4.1 and both are in a validc ategory. The result of the N-gain test in the pretest-posttest generates an N-gain score of 0.63 or a moderatec ategory. The result of the questionnaire for teachers and students are 4.75 and 4.35, respectively, or botha re in an excellent category. The study concludes that the developed natural science learning medium isf easible to be used in improving students’ critical thinking skills in natural science learning. Recommendation from the research according to the experts and teachers’ assessment is to develop thecomic so that it can accommodate content in the basic competencies in detail.